2021
DOI: 10.3390/rs13193810
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Multispectral Imagery and 3D Point Clouds from Unoccupied Aerial Systems (UAS) for Monitoring Forest Structure and the Impacts of Wildfire in Mediterranean-Climate Forests

Abstract: Wildfire shapes vegetation assemblages in Mediterranean ecosystems, such as those in the state of California, United States. Successful restorative management of forests in-line with ecologically beneficial fire regimes relies on a thorough understanding of wildfire impacts on forest structure and fuel loads. As these data are often difficult to comprehensively measure on the ground, remote sensing approaches can be used to estimate forest structure and fuel load parameters over large spatial extents. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…We thus find that there is some value in UAS-SfM, particularly in forests with gaps in the canopy or relatively low CBH, such as oak woodlands or managed stands, where some lower-canopy points are detected in the SfM process. In addition, our previous research found multispectral UAS-SfM to be useful for monitoring changes in upper-canopy structure and greenness after wildfires (Reilly et al, 2021). We also note that multi-angle views can improve detection of sub-canopy structure with UAS-SfM (Lamping et al, 2021), a factor that we could not explore as we were constrained to a nadir view by our UAS and sensor equipment.…”
Section: Modeling the Relationship Between Ladder Fuels And Burn Seve...mentioning
confidence: 87%
See 3 more Smart Citations
“…We thus find that there is some value in UAS-SfM, particularly in forests with gaps in the canopy or relatively low CBH, such as oak woodlands or managed stands, where some lower-canopy points are detected in the SfM process. In addition, our previous research found multispectral UAS-SfM to be useful for monitoring changes in upper-canopy structure and greenness after wildfires (Reilly et al, 2021). We also note that multi-angle views can improve detection of sub-canopy structure with UAS-SfM (Lamping et al, 2021), a factor that we could not explore as we were constrained to a nadir view by our UAS and sensor equipment.…”
Section: Modeling the Relationship Between Ladder Fuels And Burn Seve...mentioning
confidence: 87%
“…Since ALS data collection occurred prior to both the Tubbs and Glass Fires, changes in both forest structure and ladder fuels could be expected by the time of our field and remote sensing surveys. Reilly et al (2021) compared canopy metrics at Pepperwood between 2019 UAS-SfM data to the 2013 ALS data and found significant relationships between these methods for unburned sites. However, they did detect changes in canopy attributes with increasing wildfire severity (RdNBR).…”
Section: Data Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Each group of tasks is important in terms of minimizing damage from forest fires. This is equally true for the Russian Federation, Canada, Australia or the countries of Southern Europe [111][112][113][114][115][116][117][118][119][120][121][122][123][124][125]. Perhaps, for the Mediterranean region, these tasks are even more important, since catastrophic forest fires have been observed there in recent years.…”
Section: Discussionmentioning
confidence: 99%